Low pressure versus standard pressure pneumoperitoneum in laparoscopic cholecystectomy: a comparative study - Mandal, Arnab; Ghosh, Arindam; Bakshi, Sabyasachi (International Surgery Journal, 2020)
Background: With the establishment of laparoscopic cholecystectomy as gold standard management of cholelithiasis, the current stress is being given on increasing patient safety and reducing the post-operative morbidity associated with this procedure. An emerging trend is to use of low-pressure pneumoperitoneum in an attempt to lower the impact of pneumoperitoneum while providing adequate working space. Methods: In this prospective randomized study 66 participants were allocated into two arms i.e. low-pressure pneumoperitoneum (LPP) and standard pressure pneumoperitoneum (SPP). The necessary data were collected using laboratory investigations, clinical examination and perioperative findings. Data were analyzed using suitable statistical software. Results: Mean duration of surgery, surgical difficulty and field visualization difficulty were insignificantly greaterin LPP group than SPP group. CO2 consumption was significantly less in LPP. Incidence of bile spillage, usage of drain was insignificantly increased in LPP. Post-operative pain was significantly greater in SPP group. Time for per oral tolerance of food and incidence of nausea were significantly greater in SPP group. Standard pressure group needed significantly more tramadol injection than LPP. There were no significant haemodynamic changes in SPP group compared to LPP group. Length of hospital stay was significantly greater in SPP. Conclusions: Laparoscopic cholecystectomy in low pressure pneumoperitoneum is safe and feasible. Intra-operative complications like operative field visualization, operative difficulties, conversion rates, duration of surgery are not affected moreover, low-pressure pneumoperitoneum, decreases consumption of intra-operative CO2, post-operative pain, shoulder tip pain, need of analgesia, nausea and promotes early per oral feeding, thus reduces hospital stay.